Can Religious Coping Predict Posttraumatic Growth - Ainul Mardiah; Elida Syahriati (Faculty of Educational Sciences, Syarif Hidayatullah State Islamic University, 2015)
Abstract The aim of this study is to examine religious coping on posttraumatic growth in Acehnese. The measurements in this research are: Short Form of Posttraumatic Growth Inventory, and Brief Religious Coping. All measurements demonstrate good internal consistency reliability (α= .62- .73). Factor analyses for each measurement were conducted and the new generated factors are used in subsequent analyses. Results showed that positive religious coping can predict PTG, in the other hand negative religious coping in both type cannot predict PTG; first, type wondering about God, and feeling punished by God. Furthermore, PTG does not different on gender and types of trauma. Abstrak Tujuan dari penelitian ini adalah untuk menguji kontribusi religious coping terhadap posttraumatic growth (pertumbuhan psikologis paska trauma). Alat ukur yang digunakna untuk riset ini adalah: Short Form of Posttraumatic Growth Inventory (SF-PTGI), dan Brief Religious Coping. Semua alat ukur menunjukkan reliabilitas yang bagus (α= .62- .73). Uji faktor analisa dilakukan untuk setiap alat ukur yang digunakan, dan faktor baru yang dihasilkan seterusnya digunakan untuk analisa berikutnya. Hasil menunjukkan bahwa positive religious coping terhadap posttraumatic growth (pertumbuhan psikologis paska trauma), sementara negative religious coping tidak bisa memprediksi posttraumatic growth (pertumbuhan psikologis paska trauma), baik itu dimensi mempertanyakan Ketuhanan, dan perasaan dihukum oleh Tuhan. Lebih lanjut, tidak ada perbedaan PTG berdasarkan gender dan tipe trauma. How to Cite: Mardiah, A., Syahriati, E,. (2015). Can Religious Coping Predict Posttraumatic Growth. TARBIYA: Journal Of Education In Muslim Society, 2(1), 61-69. doi:10.15408/tjems.v2i1.1741. Permalink/DOI: http://dx.doi.org/10.15408/tjems.v2i1.1741